The Malaysian society perception on the prospect of electronic commerce / Mohd Sazili Shahibi ... [et al.] - Shahibi, Mohd Sazili; Ibrahim, Zaharudin; Abdul Kadir, Mohd Razilan; Othman, Ahmad Soufiean (Faculty of Information Management, 2005)
This research progress paper presented with purpose to study the prospect of electronic commerce application in Malaysia. These papers start with discussion about e-commerce in general. Next, the paper will present the reasons about barrier to adoption of e-commerce application. This is followed by discussion about research design and the conclusion.